Thyroid stem cells: concept and clinical implications - Nani ML; Mahkamova K; Aspinall S; Meeson A (Faculty of Medicine, Universiti Kebangsaan Malaysia Medical Centre, 2016)
Thyroid pathology is the commonest endocrine surgical problem encountered. However, the study of thyroid stem cells is relatively new in the field of stem cell research. Since the identification of thyroid stem cells in 1992, research interest in this area has been increasing mainly based on furthering our knowledge of the biology of these important cells that are thought to be responsible for tumourigenesis and propagation of cancers. This article reviews the current science and biology of thyroid stem cells and summarizes their potential role in the general management of thyroid disorders.